Supplement Use Among Athletes: Insights from Gyms in Sarajevo - Denis Čaušević; Cristina Ioana Alexe; Nedim Čović; Elena Adelina Panaet; Ensar Abazović; Raul Marian Todor; Babina Rani; Gabriel Lupu; Dan Iulian Alexe (Applied Sciences)
This study aimed to examine the habits, attitudes, and consumption patterns of food supplements (FS) among gym users in Sarajevo, Bosnia and Herzegovina, with respect to gender, age, and training experience. Understanding these behaviors is essential given the rising global trend in FS use, often without professional guidance, which can have implications for individual health and public awareness. By investigating local patterns, this study seeks to provide valuable insights into the motivations and risks associated with supplement consumption, contributing to evidence-based recommendations and policy-making in the field of fitness and nutrition. Methods: Cross-sectional data were collected from various fitness centers using an online questionnaire composed of 21 questions divided into three segments. A total of 614 participants (mean ± SD: 32.77 ± 9.82 years), including both male (67.8%) and female (32.2%) gym users, took part in the study. Results: Participants predominantly belonged to the 36–45 age group, with 70.0% (p < 0.001) reporting more than one year of regular gym attendance, and 40.4% indicating regular FS consumption (p < 0.05). Supplements were mainly used to support faster recovery (29.1%, p < 0.05) and muscle growth (25%, p < 0.05). Magnesium was the most commonly used supplement, equally favored across genders and age groups. Creatine, fish oil capsules, and multivitamins were also frequently consumed (p < 0.05). Self-prescription emerged as the predominant method of FS use (40.3%, p < 0.05), followed by advice from gym coaches (21.8%), with only 5.6% of participants receiving guidance from a nutritionist. Conclusions: The findings highlight a societal trend toward self-directed FS use, often influenced by informal sources, underscoring the importance of further research and the development of targeted, evidence-based educational strategies. Males reported higher FS consumption, with younger users more focused on muscle gain and older individuals prioritizing health maintenance. The reliance on non-expert recommendations raises concerns about the safety and effectiveness of FS usage in the fitness community.